The Pre-Deal Phase of Mergers and Acquisitions: A Review and Research Agenda - Welch, Xena; Pavićević, Stevo; Keil, Thomas; Laamanen, Tomi (Journal of Management, 2020)
Despite the long-standing research interest in the pre-deal phase of mergers and acquisitions, many important questions remain unanswered. We review and synthesize the extensive but rather fragmented research on this topic area in the fields of management, finance, accounting, and economics. We organize our review according to six themes, that is, deal initiation, target selection, bidding and negotiation, valuation and financing, announcement, and closure, which represent the main categories of activities performed during the pre-deal phase. Our review shows that most of the existing research relies on a rather high-level, simplified, and static conception of the pre-deal phase. On the basis of our review, we put forward a research agenda that calls for a more granular examination of individual activities and decisions, a more comprehensive analysis of the interplay among the different actors involved in the pre-deal phase, a better understanding of the role of the temporal dynamics, and the extension of the theoretical base from variance-based to process-based theorizing.